Service Readiness for Safe Abortion Services - Dangol, Deeb Shrestha; Gyawali, Nisha; Kumar Lal, Bibek; Joshi, Nisha Kumari; Karki, Sujan; Lamichhane, Kritee; Phuyal, Parash Prasad; Joshi, Shipra; Ghimire, Jagadishwor; Powell, Bill; Dhillon, Jina; Lynam, Anna (Journal of Nepal Health Research Council, 2024)
Background: Health service readiness is a prerequisite to accessing quality services. This study analyzes the readiness of health facilities in Nepal to provide comprehensive abortion services by focusing on the availability and quality of care.? Methods:  This is a cross-sectional study, and a multi-stage sampling approach was used to select health facilities. A total of 767 health facilities were surveyed from 30 Municipalities across the country.  Results: In a study of 767 health facilities surveyed, only 223 (29%) offered abortion services. Among them, 92% offered medical abortion, 48% provided manual vacuum aspiration, 18% offered dilation and evacuation and 18% offered medical induction. Approximately 7% of health facilities lacked trained providers yet still provided services and 29% of health facilities providing abortion services were not compliant with legal requirements. Interestingly, 13% of these facilities lacked short-acting contraceptives.  Conclusions:  Most health facilities in Nepal lack readiness for Safe Abortion Services (SAS), failing to meet minimum criteria, including to provide abortion legally. Urgent collaborative efforts among policymakers, administrators, and healthcare providers are needed to align with Nepal's Sustainable Development Goals and address gaps in safe abortion service availability. This includes policy updates, strengthening Public-Private Partnerships (PPPs), and ensuring comprehensive SAS implementation and financing as part of essential health services.Keywords: Health facility; listed facility; post abortion care; safe abortion; service readiness.